Anaerobic derivates of mitochondria and peroxisomes in the free-living amoeba Pelomyxa schiedti revealed by single-cell genomics - Kristína Záhonová; Sebastian Cristian Treitli; Tien Le; Ingrid Škodová-Sveráková; Pavla Hanousková; Ivan Čepička; Jan Tachezy; Vladimír Hampl (BMC Biology, 2022)
Abstract Background Mitochondria and peroxisomes are the two organelles that are most affected during adaptation to microoxic or anoxic environments. Mitochondria are known to transform into anaerobic mitochondria, hydrogenosomes, mitosomes, and various transition stages in between, collectively called mitochondrion-related organelles (MROs), which vary in enzymatic capacity. Anaerobic peroxisomes were identified only recently, and their putatively most conserved function seems to be the metabolism of inositol. The group Archamoebae includes anaerobes bearing both anaerobic peroxisomes and MROs, specifically hydrogenosomes in free-living Mastigamoeba balamuthi and mitosomes in the human pathogen Entamoeba histolytica, while the organelles within the third lineage represented by Pelomyxa remain uncharacterized. Results We generated high-quality genome and transcriptome drafts from Pelomyxa schiedti using single-cell omics. These data provided clear evidence for anaerobic derivates of mitochondria and peroxisomes in this species, and corresponding vesicles were tentatively identified in electron micrographs. In silico reconstructed MRO metabolism harbors respiratory complex II, electron-transferring flavoprotein, a partial TCA cycle running presumably in the reductive direction, pyruvate:ferredoxin oxidoreductase, [FeFe]-hydrogenases, a glycine cleavage system, a sulfate activation pathway, and an expanded set of NIF enzymes for iron-sulfur cluster assembly. When expressed in the heterologous system of yeast, some of these candidates localized into mitochondria, supporting their involvement in the MRO metabolism. The putative functions of P. schiedti peroxisomes could be pyridoxal 5′-phosphate biosynthesis, amino acid and carbohydrate metabolism, and hydrolase activities. Unexpectedly, out of 67 predicted peroxisomal enzymes, only four were also reported in M. balamuthi, namely peroxisomal processing peptidase, nudix hydrolase, inositol 2-dehydrogenase, and d-lactate dehydrogenase. Localizations in yeast corroborated peroxisomal functions of the latter two. Conclusions This study revealed the presence and partially annotated the function of anaerobic derivates of mitochondria and peroxisomes in P. schiedti using single-cell genomics, localizations in yeast heterologous systems, and transmission electron microscopy. The MRO metabolism resembles that of M. balamuthi and most likely reflects the state in the common ancestor of Archamoebae. The peroxisomal metabolism is strikingly richer in P. schiedti. The presence of myo-inositol 2-dehydrogenase in the predicted peroxisomal proteome corroborates the situation in other Archamoebae, but future experimental evidence is needed to verify additional functions of this organelle.